Minimum Wages and Consumer Credit: Effects on Access and Borrowing - Dettling, Lisa J; Hsu, Joanne W (Review of Financial Studies, 2021)
Abstract This paper examines how minimum wages affect lender and borrower interactions with consumer credit markets. We find that higher state minimum wages increase the supply of unsecured credit, reduce payday loan usage, decrease delinquency, and increase credit scores. Overall, minimum wages reduce borrowing costs and have positive spillover effects on disposable income and liquidity. A back-of-the-envelope of the cost savings indicates that higher minimum wages increase disposable income by 1.3% more than implied by estimates of the direct effect on earnings.